2012
DOI: 10.3109/02656736.2012.695428
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of combined regional hyperthermia and gemcitabine for locally advanced or metastatic pancreatic cancer

Abstract: Regional hyperthermia combined with gemcitabine is well tolerated and active in patients with locally advanced pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 29 publications
3
33
0
Order By: Relevance
“…In GEM chemotherapy, nuclear factor kappa B (NF-κB), a transcription factor, is activated through immunological mechanisms, and this is regarded as one of the causes of GEM resistance development. Heat shock protein induced by concurrent HCR reportedly exerts inhibitory actions on NF-κB activity (18,19), which is regarded as being a mechanism underlying the antitumor effect of HCR. Accordingly, for patients whose performance status is satisfactory, hyperthermia is considered to contribute to prolonged survival Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…In GEM chemotherapy, nuclear factor kappa B (NF-κB), a transcription factor, is activated through immunological mechanisms, and this is regarded as one of the causes of GEM resistance development. Heat shock protein induced by concurrent HCR reportedly exerts inhibitory actions on NF-κB activity (18,19), which is regarded as being a mechanism underlying the antitumor effect of HCR. Accordingly, for patients whose performance status is satisfactory, hyperthermia is considered to contribute to prolonged survival Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Ishikawa et al [63] 18 None c-LRHT (40 min.) bring the temperature below the required temperature, as reported by Yamada et al [54]; although their target temperature was 42.5 C, only in five of the 17 patients the tumour was heated to more than the required 42 C. In this review, only one subcutaneous fatty burn was reported in one patient.…”
Section: Thermal Dosimetrymentioning
confidence: 99%
“…Locoregional hyperthermia was used in eight studies, with heating of tumour and surrounding tissue either radiative (using radiofrequency waves; 63 patients) [62,64] or capacitive (using electrodes; 126 patients) [53,58,60,63,65,66]. Treatment times varied from 40-60 min.…”
Section: Patient Characteristics and Treatment Regimensmentioning
confidence: 99%
See 1 more Smart Citation
“…The Japanese Trial (Ishikawa et al 2012) [32] Patients were administered gemcitabine 1,000 mg/m2 on days 1, 8 and 15 every 4 weeks. Loco-regional hyperthermia (capacitative system) was delivered once per week, a day preceding the gemcitabine infusion.…”
Section: The German Study I (Hager Et Al 2006) [24]mentioning
confidence: 99%